A self-regulation-based intervention to increase physical activity in cancer patients - Ungar, Nadine; Sieverding, Monika; Ulrich, Cornelia; Wiskemann, Joachim (Psychology, health & medicine, 2016)
The study examined whether a behavior-change intervention focusing on self-regulatory strategies and emphasizing role model support increases physical activity (PA) among insufficiently active (not meeting PA guidelines of 150 min/week) cancer patients. Ambulatory cancer patients [N = 72; 54% female; M = 56 years, SD = 12.34; most with breast or colon cancer (34, 15%)] were enrolled in the MOTIVACTION-study, a 4-week intervention (1-hr counseling, followed by weekly phone calls), with pretest (T1), posttest (T2) and a 10-week follow-up (T3). Participants were randomized to either an exercise or to a stress management intervention (active control). The exercise intervention emphasized self-regulatory strategies (e.g. action- and coping planning and self-monitoring); patients were also encouraged to contact a physically active same-sex role model as a potential exercise partner. The active control condition consisted of coping and relaxation techniques. Sixty-seven patients remained in the study and completed the SQUASH assessment of PA and a measure of perceived stress. PA was validated by Actigraph accelerometry. At T2, 46% of the patients in the exercise group and 19% of stress management patients increased their activity levels to meet PA guidelines (>150 min/week; χ2(1) = 5.51, p = .019). At T3, participants in the exercise intervention maintained their exercise level (46%), but also 31% of the stress management patients met the guidelines. All patients reported reductions in perceived stress. Additional analyses comparing patients in the exercise group by role model contact (63% realized contact) revealed that those who had contact with their role model were significantly more likely to adhere to the recommended guidelines (T2:50%; T3:64%) compared to those who did not have contact with a role model (T2:39%; T3:15%), suggesting the potential of mobilizing role model support to facilitate PA. In sum, cancer patients may not only benefit from an exercise intervention emphasizing self-regulation, but also from stress management, regarding both reducing stress and increasing PA.